Teacher Discomfort/Well-Beings: A Case of Three Bilingual Intercultural Schools of Arantepacua and Capacuaro Michoacán, México - León León, Giselle (2014)
With the purpose of knowing the relationship between the teachers´ well-being and discontentment as an opposing pairing and the association to personal, institutional and social factors from an indigenous-intercultural perspective, a study was conducted in three bilingual intercultural primary education centers: two from Arantepacua and one from Capacuaro; both are P’urhépechas peoples from the Michoacán State.  This was a qualitative phenomenological study using in-depth interviewing research and one survey. Among the results of this study, the prevalence of discontentment mainly in social factors, such as migration, discipline, changes in education policies and teacher training stand out. Another factor that demonstrates discontentment was the institutional one in relation to the teachers´ excessive workload.  On the other hand, well-being was identified in individual factors because they are self-sufficient.